Uzasadnienia orzeczeń Trybunału Konstytucyjnego w kwestii dopuszczalności wniosków i skarg konstytucyjnych a konstytucyjne standardy sprawiedliwości proceduralnej: [Justification of the Constitutional Court’s decisions on the admissibility of constitutional complaints and applications and constitutional standards of procedural fairness] (Studia Prawnicze / The Legal Studies, 2014)
Trybunał Konstytucyjny podkreśla, że do istoty konstytucyjnego prawa do sądu należy sprawiedliwość proceduralna. To, że Trybunał Konstytucyjny nie sprawuje wymiaru sprawiedliwości, nie zwalnia go z obowiązku przestrzegania standardów sprawiedliwości proceduralnej, w szczególności tych określonych w jego własnym orzecznictwie. Wszak jest organem władzy sądowniczej. Wypada wspomnieć, że w jednym ze swoich orzeczeń Trybunał Konstytucyjny wskazał na zasadność szerokiej wykładni pojęcia „sąd”, obejmując nim także Trybunały. Trybunał Konstytucyjny określa siebie mianem „sądu prawa”, zaznaczając, że taki status przyznała mu ustawa zasadnicza. The author focuses on how the Constitutional Court formulates reasons for its decisions on the admissibility of the constitutional complaints and applications. The Court’s practice is confronted with constitutional standards of procedural fairness. The author draws attention to the need to ensure the predictable nature of the decisions of the Constitutional Court by the consistency of its case-law, in particular with regard to the concept of the matters referred to in Art. 191 paragraph 2 of the Constitution. The author analyzes the requirement to indicate in what way the freedom or the applicant’s constitutional rights have been violated, having regard to the obligation to disclose the motives of the Court’s ruling in a clear manner. In the author’s opinion, the obligation to justify the decision in such a way that the applicant verify the judge reasoning also applies to the decision on account of appeal against a decision to refuse to grant constitutional complaint further. The author looks at the ground for refusal of the application or the constitutional complaint further action from the perspective of, on the one hand, the obligation of a comprehensive examination of the facts, on the other hand, the obligation to smooth hearing within a reasonable time.